2013
DOI: 10.1155/2013/967805
|View full text |Cite
|
Sign up to set email alerts
|

Closing a Window for Massive Photons

Abstract: Working with the assumption of non-zero photon mass and a trajectory that is described by the non geodesic world line of a spinning top we find, by deriving new astrophysical bounds, that this assumption is in contradiction with current experimental results. This yields the conclusion that such photons have to be exactly massless.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…The latter are particularly attractive, since they imply the conservation of the invariant momentum squared, which is associated with mass. Interestingly, it is found that the deviations from usual geodesics increase with decreasing mass [27,33]. However, the transition to zero mass is not continuous.…”
Section: Introductionmentioning
confidence: 99%
“…The latter are particularly attractive, since they imply the conservation of the invariant momentum squared, which is associated with mass. Interestingly, it is found that the deviations from usual geodesics increase with decreasing mass [27,33]. However, the transition to zero mass is not continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the death and lack of solid experimental proof [1]- [4], it is generally agreed (perhaps believed) that photons have no mass. Though this notion of a zero-mass photon has been questioned over the years [5]- [9], this deeply entrenched notion has been deduced from the logical fusion of two (seemingly) immutable facts of experience so well supported by experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in the present reading is the source coupled Equation (1), and not not (3) and as such, we shall not-after the present section-come back to this Equation (3). From these two tensor Equations (1) and (3), we can write down the four Maxwell's equations which we are used to, and, much readily identify with, i.e. :…”
Section: Maxwellian Electrodymanicsmentioning
confidence: 95%
“…Despite the inconclusive experimental evidence (see e.g., Refs. [1]- [10]), photons are largely believed to be massless and the most compelling of all evidence there-it is said-is found in their physical and natural manifestation as long ranged and long lived particles (e.g., Refs. [11]- [13]).…”
Section: Introductionmentioning
confidence: 99%